DERIVATIVE OF A FUNCTION AND ITS APPLICATIONS THROUGH THE MAPLE SOFTWARE PACKAGE - Baxtiyor Usmonov; Zarinabonu Abdufayozova (Bright Mind Publishing, 2025)
This article analyzes the process of teaching the derivative of a function and its applications using the Maple software package. The differential calculus section of mathematical analysis not only provides students with fundamental knowledge, but also allows for a deeper understanding of concepts through practical programming tools. Using the Maple software package to compute derivatives of functions and to represent their geometric interpretations graphically helps students gain a clearer understanding. The capabilities of the Maple software in differentiating functions, calculating derivatives, and visualizing results are discussed. The results of the study show that teaching with the Maple package enhances the practical reinforcement of theoretical knowledge, facilitates comprehension through visualization, and develops independent working skills. Therefore, the Maple software package plays a significant role in teaching mathematical analysis in modern education.
Keywords: Function derivative, function differentiation, operator, Maple, differential calculus, mathematical modeling, graphical visualization, mathematics education, physics, economics, biology, ecology, code.